PENGARUH WORK LIFE BALANCE DAN BEBAN KERJA TERHADAP STRES KERJA KARYAWAN PT PLN (PERSERO) UP3 MADIUN - Tiara Amelia Anisa Putri; Kustini Kustini (International Journal of Multidisciplinary Research and Literature, 2023)
Human resource are an important part in the operation of a company to achieve goals, where human resources actively manage other resources. In order for employees in the company to achieve good targets and continue to increase, leaders must also pay attention to the conditions of employees properly. The purpose of this study is to determine the influence of Work Life Balance and Workload on Employee Work Stress at PT PLN (Persero) UP3 Madiun. This study uses a quantitative method with a population and sample size of 52 employees, where the sample technique used is saturated sample. The data collection methods were carried out through questionnaire distribution. The data analysis technique used is Partial Least Square (PLS). The results showed that Work Life Balance and Workload were able to influence Employee Work Stress at PT PLN (Persero) UP3 Madiun